Chemical and Enzymatic Approaches to Esters of sn‐Glycero‐3‐Phosphoric Acid. Issue 29 (7th May 2021) - Semproli, Riccardo; Robescu, Marina S.; Cambò, Mattia; Mema, Klodiana; Bavaro, Teodora; Rabuffetti, Marco; Ubiali, Daniela; Speranza, Giovanna
Abstract: Esters of sn ‐glycero‐3‐phosphoric acid (GPAE) are derivatives of glycerophospholipids in which both the fatty acid chains in sn ‐1 and sn ‐2 positions are removed. Phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), and phosphatidylserine (PS) are the most abundant glycerophospholipids in Nature. Their deacylated derivatives find application in many industrial sectors; for example, sn ‐glycero‐3‐phosphocholine (GPC) is useful as a cognitive enhancer and as a food ingredient, whereas sn ‐glycero‐3‐phosphoinositol (GPI) acts as a natural anti‐inflammatory agent. This minireview covers the state‐of‐the‐art of chemical and biocatalytic methods for the obtainment of these lipid‐derived components. Abstract : Esters of sn ‐glycero‐3‐phosphoric acid (GPAE) are highly polar, water‐soluble molecules endowed with important biological and pharmacological activities. Methods for GPAE manufacturing are based either on enzymatic deacylation of glycerophospholipids contained in lecithin or on a multi‐step total synthesis from commercially available building blocks. Current manufacturing routes to GPAE and their complex biological functions are reviewed herein.